Methods Of Developing Technical Creativity Of Primary School Students - Karimov Hamidbek Otakhanovich (Academia One, 2023)
This article describes the role and importance of ways to develop scientific, technical, artistic creativity through the use of new pedagogical technologies such as modulartechnical experiments, morphological analysis, brainstorming, problem situations aimed at developing the level of knowledge, skills and abilities of primary school students
Keywords: continuing education; creative ability; technique; morphological analysis